Backstroke Teaching Aid #1 - Rushall, B. S. (1999)
The collage of sequences from some of the world's best backstrokers (K. Egerszegi, B. Fridgewater, S. Theloke, M. Lopez-Zubero) are presented as teaching aids in Dr. Rushall's Stroke Clinics. Each item is presented to show important features of the stroke that should be adapted to each individual's capabilities.